2019
DOI: 10.1080/09537287.2019.1567859
|View full text |Cite
|
Sign up to set email alerts
|

A dimensional analysis of stakeholder assessment of project outcomes

Abstract: Driven by an interest in developing a deeper understanding of stakeholder interests, this study undertakes a dimensional analysis of how different stakeholders assess project outcomes. Most importantly, in our analysis, we take into consideration the largely unaccounted-for conceptual difference between project success and project failure. Data were collected over a two-year period (between 2013 and 2015) from 1631 project stakeholders in nine countries. We analysed the survey data using three-way Multidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 139 publications
0
33
0
Order By: Relevance
“…Key project stakeholders within organisations may express different preferences for individual projects within their portfolio given limited resources. Project stakeholders with a preference for predictability, high task certainty and who are risk averse may support projects which are designed within the realm of pre-existing organisational competencies (Chipulu et al 2019).…”
Section: The Project Portfolio Imperativementioning
confidence: 99%
“…Key project stakeholders within organisations may express different preferences for individual projects within their portfolio given limited resources. Project stakeholders with a preference for predictability, high task certainty and who are risk averse may support projects which are designed within the realm of pre-existing organisational competencies (Chipulu et al 2019).…”
Section: The Project Portfolio Imperativementioning
confidence: 99%
“…For example, various studies have identified human and related factors (including project team management) as critical factors for project success (see, for example, Chan, Scott, and Chan 2004;Belout and Gauvreau 2004;Scott-Young and Samson 2008;Ojiako, Johansen, and Greenwood 2008;Chipulu et al 2016Chipulu et al , 2019. Interestingly, by the interviewees focussing their discussion on the time, cost, and quality factor, it will appear that this notion of project success, while arguably project management scholarship has moved beyond (Shenhar et al 2001;Chipulu et al 2019), still holds reverence among project management practitioners. Despite this being the case, it is important that we acknowledge that the literature does emphasize that the valuable resource by itself does not necessarily give a competitive advantage (Baia, Ferreira, and Rodrigues 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such an understanding is important as it is inevitable that tensions will exist between these different levels (Chandrasekaran, Linderman, and Schroeder 2012), and not managing these tensions is a major source of risk to enhanced project performance and sustained business competitiveness (Marshall et al 2019;Al-Mazrouie et al 2020). Organizations will generally consist of different stakeholders which research should not treat as cohesive or homogeneous decision-making units (Ojiako et al 2014(Ojiako et al , 2015Chipulu et al 2019). However, these tensions require management despite the reality that practitioners across different levels of an organization are likely to continue to maintain informal and professional ties that last well beyond the completion of a specific project.…”
Section: The Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, construction projects have measured performance of construction activities focussing on time, quality, and cost (Jonsson and Rudberg 2017), i.e. the 'Iron Triangle' (Atkinson 1999;Chipulu et al 2019). However, balancing project performance in the 'Iron Triangle' is dependent on wellfunctioning construction logistics that ensures that materials and resources are delivered to, and retrieved from, site when needed (Dubois, Hulth en, and Sundquist 2019;Ying, Tookey, and Seadon 2018).…”
Section: Evaluating Logistics Performancementioning
confidence: 99%